Perlindungan Hukum Terhadap Hak-Hak Korban Kejahatan Seksual Berdasarkan Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual - Muslim Harahap; Sugih Ayu Pratitis; Rehulina Rehulina (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
From January to July 2020 cases of violence against adult women increased from 3020 people to 3059 victims, even sexual violence in children increased to 2556. The purpose of this study was to find out the state responsibility of the rights of victims of crime; The application of law to victims of sexual crimes and obstacles and challenges in the application of the rights of victims of sexual crimes. This research is a normative juridical legal research, namely research conducted based on secondary data. The nature of this research is descriptive analysis. The data used in this study are secondary data, namely data obtained from literature research in the form of legal materials. Data collection techniques are literature and field. The results showed that the Criminal Act of Sexual Violence could provide legal protection for victims and be able to restore the rights of the Sikorban by providing legal treatment, recovery and protection.